Investment Analysis and Management - V. N. Salin; O. Yu. Sitnikova; O. G. Tret’yakova; E. P. Shpakovskaya (Управленческие науки, 2023)
The rate of economic growth is largely determined by the level of investment activity, as well as by the scale of investment activity, the expansion of which requires an increase in investment and its efficiency. Objective economic and statistical assessment of investment provides an opportunity to analyze the results of the process of management of this sphere of activity. The purpose of the work is to investigate changes in the composition and structure of investments, factors influencing and limiting the growth of their funding sources, as well as to analyze the dynamics of investment activity in the Russian Federation in recent years on the basis of data from the Federal State Statistics Service. The paper provides definitions of investments and considers their types. In the course of the study, the authors applied such scientific methods as structural and dynamic data analysis, theoretical research in the form of generalization, comparison and special analytical procedures. The results obtained can be used to prioritise investment management and management decisions.